Adverbia Temporal (AT) Berpreposisi dalam Bahasa Inggris - Lily Marliah (Jurnal Sosioteknologi, 2006)
The title of this research is called " Adverbia Temporal Berpreposisi dalam Bahasa Inggris" or "žThe Prepositional Phrase of Adverb of Time (AT) in English"Ÿ: This reseach focuses on: i. What the structures of Adverb of Time are ; ii what prepositions of the Adverb of Time and their positions are; iii what temporal meaning of the adverb of time are; iv which prepositions of the Adverb of Time can be deleted or obligated in AT phrases . The method used in the research is descriptive and synchronic linguistics. The analysis based on the classificaton of data results in : First, the prepositional phrase of AT in English are formed by preposition/s + noun/ noun phrase, and preposition/s + other constituents . Second, the are 52 kinds of prepo- sition divided into 19 single prepositions forming AT such as since; 9 double prepo- sitions, e.g. up to; 20 single prepositions pairs,e.g., since___between ; 4 double preposition pairs,e.g., over about__from__to.; the positions of the AT are Initial Position (IP) or pre position, Mid Position (MP) or interposition, End Position (EP) or postposition. Third, the temporal meaning of the AT are position of time (forward spand, backward span, and neutral), duration, frequency Fourth, certain constituents in AT phrases, and the use of dynamic and static verbs in sentences may infuence the deletion/ obligation of certain prepositions of AT.